[tex]\displaystyle\bf\\\frac{Cos^{2} (\pi +\alpha )}{Cos^{2}\Big(\alpha -\frac{3\pi }{2} \Big) } -\frac{Sin^{2} \alpha +Cos^{2} \alpha }{Cos^{2} \Big(\alpha +\frac{\pi }{2} \Big)} +1=\frac{Cos^{2}\alpha }{Sin^{2} \alpha } -\frac{1}{Sin^{2} \alpha } +1=\\\\\\=\frac{Cos^{2} \alpha -1}{Sin^{2}\alpha } +1=\frac{-Sin^{2}\alpha }{Sin^{2} \alpha } +1=-1+1=0[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
[tex]\displaystyle\bf\\\frac{Cos^{2} (\pi +\alpha )}{Cos^{2}\Big(\alpha -\frac{3\pi }{2} \Big) } -\frac{Sin^{2} \alpha +Cos^{2} \alpha }{Cos^{2} \Big(\alpha +\frac{\pi }{2} \Big)} +1=\frac{Cos^{2}\alpha }{Sin^{2} \alpha } -\frac{1}{Sin^{2} \alpha } +1=\\\\\\=\frac{Cos^{2} \alpha -1}{Sin^{2}\alpha } +1=\frac{-Sin^{2}\alpha }{Sin^{2} \alpha } +1=-1+1=0[/tex]